1997
DOI: 10.1097/00006534-199712000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Island Adipofascial Flap Based on Distal Perforators of the Radial Artery: An Anatomic and Clinical Investigation

Abstract: Reconstruction of soft-tissue defects of the hand with exposed tendons, joints, and bone represents a challenge to the plastic surgeon, and such defects necessitate flap coverage to preserve hand function and to protect its vital structures. Reported here is the study of an island adipofascial flap based solely on the distal five to eight septocutaneous perforators of the radial artery and their venae comitantes. Designing the flap in the form of an island with skeletonization of the distal perforators of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Distally based fasciocutaneous flaps based on a subcutaneous pedicle including the cephalic vein and the lateral antebrachial cutaneous nerve and supplied distally by the perforators from the radial artery have been reported. [12][13][14][15] However, few studies have clearly demonstrated the finer framework of the vascular connections among these perforators within the integument itself, which determines the vascular anatomical basis and which is critical for the survival of any flap based on these perforators. The exact vascular territory of the distally based island flap remains unclear.…”
mentioning
confidence: 99%
“…Distally based fasciocutaneous flaps based on a subcutaneous pedicle including the cephalic vein and the lateral antebrachial cutaneous nerve and supplied distally by the perforators from the radial artery have been reported. [12][13][14][15] However, few studies have clearly demonstrated the finer framework of the vascular connections among these perforators within the integument itself, which determines the vascular anatomical basis and which is critical for the survival of any flap based on these perforators. The exact vascular territory of the distally based island flap remains unclear.…”
mentioning
confidence: 99%
“…3,5 The principle of flap vascular supply via perforators can be applied in the radial-forearm flap.…”
Section: Discussionmentioning
confidence: 99%
“…The reversed ulnar forearm flap described by Lovie is a septocutaneous flap [1][2][3][4][5] based on the septocutaneous perforators of the ulnar artery, but it can also be harvested as a fascial flap. 2 The use of the fascial flap is indicated in patients with soft tissue defects of the hand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Therefore, neurofasciocutaneous flaps or neurovenofasciocutaneous flaps may be more suitable terms. 22 In 1997, El-Khatib and Zeidan 23 introduced an anatomic study and 8 cases using an island adipofascial flap based on distal perforators of the radial artery located between 2À7 cm from the radial styloid process.…”
Section: Discussionmentioning
confidence: 99%